Critical theory and its controversies - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 2016)
The essay explicates the debates within the Critical School, including the major controversy between Habermas and Gadamer. While the debates are within the “inner circle” of this school, external questions enter concerning the status of sciences, technology, life world, values, language and the possibility of reflective emancipation. Thus, the question of scientific “neutrality” becomes relevant with respect to objective rationality, resulting in a debate whether reason is in a position to justify itself without becoming circular. The critical part of the essay consists of the demonstration that reflective reason offers another level of discursive practice, capable of adjudicating the issues in terms of primacy of experience – in a broadest sense of the term.